2020
DOI: 10.3748/wjg.v26.i34.5118
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture improved lipid metabolism by regulating intestinal absorption in mice

Abstract: BACKGROUND Non-alcoholic fatty liver disease (NAFLD), in which abnormal lipid metabolism plays an important role in disease progression, has become a pandemic. Abnormal lipid metabolism, for example an increased fat intake, has been thought to be an initial factor leading to NAFLD. The small intestine is the main site of dietary lipid absorption. A number of clinical trials have shown that acupuncture has positive effects in the regulation of lipid metabolism, which is closely associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…After digestion of dietary fat, the predominant lipid across the apical membrane and then enters the enterocyte via both passive diffusion and protein-facilitated fatty acid transfer . A larger number of proteins, including CD36, I-FABP, and FATP4, play a crucial role in promoting fatty aicd transport. , After uptake by enterocytes, fatty acids are transported into the endoplasmic reticulum by MTTP and then packaged as chylomicron (CM) with apolipoproteins, such as ApoB, ApoA-I, and ApoA-IV. , Studies had demonstrated that suppressing intestinal fat absorption exerts a potential effect on preventing and treating obesity. , Therefore, we explored the lipid absorption-related proteins and we hypothesized that Gln can reduce intestinal fatty acid absorption considering previous findngs on the beneficial effects of Gln supplementation in several clinical conditions. Surprisingly, our study showed that Gln administration further upregulated the protein levels of ApoB48, I-FABP, and CD36, indicating that more fatty acids were absorbed and transported into epitheliums.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After digestion of dietary fat, the predominant lipid across the apical membrane and then enters the enterocyte via both passive diffusion and protein-facilitated fatty acid transfer . A larger number of proteins, including CD36, I-FABP, and FATP4, play a crucial role in promoting fatty aicd transport. , After uptake by enterocytes, fatty acids are transported into the endoplasmic reticulum by MTTP and then packaged as chylomicron (CM) with apolipoproteins, such as ApoB, ApoA-I, and ApoA-IV. , Studies had demonstrated that suppressing intestinal fat absorption exerts a potential effect on preventing and treating obesity. , Therefore, we explored the lipid absorption-related proteins and we hypothesized that Gln can reduce intestinal fatty acid absorption considering previous findngs on the beneficial effects of Gln supplementation in several clinical conditions. Surprisingly, our study showed that Gln administration further upregulated the protein levels of ApoB48, I-FABP, and CD36, indicating that more fatty acids were absorbed and transported into epitheliums.…”
Section: Discussionsupporting
confidence: 92%
“…9,30 Studies had demonstrated that suppressing intestinal fat absorption exerts a potential effect on preventing and treating obesity. 31,32 Therefore, we explored the lipid absorption-related proteins and we hypothesized that Gln can reduce intestinal fatty acid absorption considering previous findngs on the beneficial effects of Gln supplementation in several clinical conditions. Surprisingly, our study showed that Gln administration further upregulated the protein levels of ApoB48, I-FABP, and CD36, indicating that more fatty acids were absorbed and transported into epitheliums.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Electroacupuncture combined with lifestyle control can effectively treat patients with NAFLD by reducing serum leptin levels, increasing the sensitivity of hepatocytes to insulin and improving IR ameliorating blood glycolipid metabolism and reducing hepatic fat, waist circumference and waist-to-hip ratio 64 , 65 , 66 . In addition, acupuncture has been shown to ameliorate NAFLD by regulating lipid metabolism 67 , 68 , 69 , 70 , improving IR 71 and ER stress 70 , 72 , 73 , alleviating oxidative stress 68 , 74 , inhibiting the expression of inflammatory cytokines 68 , 69 , 75 , and alleviating steatosis, necrosis and inflammatory cell infiltration of liver tissue in NAFLD rat model. Furthermore, acupuncture can alleviate bullous steatosis of liver tissue 76 , 77 , 78 , and the expansion and disorder of rough endoplasmic reticulum 73 in NAFLD rat model.…”
Section: Therapeutic Effects and Mechanisms Of Tcm In Treating Nafldmentioning
confidence: 99%
“…In addition, Huang et al [ 30 ] assessed 102 patients with obesity with NAFLD treated by electroacupuncture and found that the electroacupuncture of “Feng long” (ST40) and “Zu san li” (ST36) could improve the hemorheological indices of patients, decrease TC and TG levels, and produce lipolysis, thus regulating their metabolic state. Han et al [ 31 ] assessed the effects of acupuncture “Zu san li” (ST36), “Guan yuan” (CV4), and “Yong quan” (KI1) in the context of a NAFLD mouse model with deficient methionine and choline, demonstrating that acupuncture could reduce the accumulation of abdominal fat, inhibit the absorption of lipids in the small intestine, and downregulate the level of blood lipids in mice, thus proving that acupuncture could reduce the accumulation of abdominal fat in the case of abnormal liver metabolism and may have different beneficial effects on improving lipid metabolism. The above evidence demonstrates that acupuncture treatment can not only regulate the lipid metabolism in the liver but also affect the inhibition of lipid absorption in the small intestine to adjust the lipid metabolism of the body to improve NAFLD; however, the mechanisms underpinning “the inhibition of lipid absorption in the small intestine” remain unclear.…”
Section: Acupuncture Improves Lipid Metabolism Disorder In Nafldmentioning
confidence: 99%